Exploring Alzheimer's disease prediction with XAI in various neural network models - Rahman, Quazi Ashikur; Shad, Hamza Ahmed; Asad, Nashita Binte; Bakshi, Atif Zawad; Mursalin, S.M Faiaz (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.